Upstream Competition and Downstream Buyer Power. - Smith, H; Thanassoulis, J (Department of Economics (University of Oxford), 2009)
It is often claimed that large buyers wield buyer power. Existing theories of this effect generally assume upstream monopoly. Yet the evidence is strongest with upstream competition. We show that upstream competition can yield buyer power for large buyers by generating supplier-level volume uncertainty - a feature that emerges from case study evidence of upstream competition - so the negotiated price depends on the seller’s cost expectation. By analyzing the effect of market structure changes on seller cost expectations the paper gives insights on three key policy-relevant questions around buyer power: (i) who wields it and under what circumstances (ii) does a downstream merger alter the buyer power of other buyers (so-called waterbed effects); and (iii) how are the incentives to invest in upstream technology altered by the creation of large downstream firms?